Comparing the Effects of Propofol Infusion and Inhalation Isoflurane on Hemodynamic Variations and Depth of Anesthesia in Cataract Surgery Patients - M khakzad (Babol University of Medical Sciences, 2019)
BACKGROUND AND OBJECTIVE: In cataract surgery, given that most patients are older people, surgery with general anesthesia requires better hemodynamic control along with maintaining the depth of anesthesia. The present study was conducted to compare the effects of propofol and isoflurane on hemodynamic variations and depth of anesthesia in cataract surgery patients. METHODS: The present clinical trial was conducted among 60 patients who were cataract surgery candidates. The patients were randomly assigned to propofol group (n = 30) and isoflurane group (n = 30). One µg/kg fentanyl and one mg/kg intravenous lidocaine were administered in both groups and anesthesia was induced using 1.5 – 2.5 mg/kg propofol. In order to maintain anesthesia, 50 – 75 µg/kg/min propofol was administered in the first group and 1% isoflurane was administered in the second group. Depth of anesthesia, hemodynamic variations, recovery time, wake-up time, nausea and vomiting were recorded and compared in the two groups. FINDINGS: Depth of anesthesia was similarly below 60 in both groups at different times. Hemodynamic variations were not significantly different in the two groups. Mean recovery time in propofol and isoflurane groups was 20.56 and 15.4 minutes, respectively (p<0.001), and wake-up time in the two groups was 8.83 and 7.16 minutes, respectively (p= 0.004). CONCLUSION: The results showed that there was no difference between the effects of these two drugs on hemodynamics and depth of anesthesia, but recovery time and wake-up time in propofol group were significantly higher than isoflurane group.